Games and fieldwork in agriculture: A systematic review of the 21st century in economics and social science - Hernández Aguilera, J. Nicolas; Mauerman, Max; Herrera, Alexandra; Vasilaky, Kathryn; Baethgen, Walter E.; Loboguerrero Rodriguez, Ana María; Diro, Rahel; Tesfamariam Tekeste, Yohana; Osgood, Daniel (MDPI, 2020)
Games are particularly relevant for field research in agriculture, where alternative experimental designs can be costly and unfeasible. Games are also popular for non-experimental purposes such as recreating learning experiences and facilitating dialogue with local communities. After a systematic review of the literature, we found that the volume of published studies employing coordination and cooperation games increased during the 2000–2020 period. In recent years, more attention has been given to the areas of natural resource management, conservation, and ecology, particularly in regions important to agricultural sustainability. Other games, such as trust and risk games, have come to be regarded as standards of artefactual and framed field experiments in agriculture. Regardless of their scope, most games’ results are subject to criticism for their internal and external validity. In particular, a significant portion of the games reviewed here reveal recruitment biases towards women and provide few opportunities for continued impact assessment. However, games’ validity should be judged on a case-by-case basis. Specific cultural aspects of games might reflect the real context, and generalizing games’ conclusions to di erent settings is often constrained by cost and utility. Overall, games in agriculture could benefit from more significant, frequent, and inclusive experiments and data—all possibilities o ered by digital technology. Present-day physical distance restrictions may accelerate this shift. New technologies and engaging mediums to approach farmers might present a turning point for integrating experimental and non-experimental games for agriculture in the 21st century.